(1022) Agricultural Prices "Bases of Setting and Control" أسعار المنتجات الزراعية "أسس التحديد و الرقابة - Saad Taha Allam. (INP., 2022)
Agriculture remains the dominant sector in most developing economies, playing a crucial role in economic growth and national income. It serves as a primary source of employment, provides essential raw materials for industries, and ensures food security. The expansion of agricultural production is vital to prevent inflationary pressures caused by rising food prices. Additionally, agriculture is a key contributor to foreign exchange earnings, as many developing nations rely on agricultural exports before achieving industrial maturity. Until these countries can sustain themselves through manufactured goods exports, agricultural development must be prioritized to support economic stability and growth.